Ecological Evaluation Index continuous formula (EEI-c) application: a step forward for functional groups, the formula and reference condition values - ORFANIDIS, S.; PANAYOTIDIS, P.; UGLAND, K. (Mediterranean Marine Science, 2011)
The Ecological Evaluation Index continuous formula (EEI-c) was designed to estimate the habitat- based ecological status of rocky coastal and sedimentary transitional waters using shallow benthic macrophyte communities as bioindicators. This study aimed to remedy the weaknesses of the currently used EEI methodology in: (1) ecological status groups (ESG), (2) the formula, and (3) reference condition values. A cluster analysis of twelve species traits was used to delineate ESGs. Two main clusters (ESG I, late-successional; ESG II, opportunistic) were identified that were hierarchically divided into three and two sub-clusters, respectively: ESG I comprised thick perennial (IA), thick plastic (IB) and shade-adapted plastic (IC) coastal water species, and angiosperm plastic (IA), thick plastic (IB) and shade-adapted plastic (IC) transitional water species. ESG II comprised fleshy opportunistic (IIB) and filamentous sheet-like opportunistic (IIA) species both in coastal and transitional waters. To avoid discrete jumps at the boundaries between predefined ecological categories, a hyperbolic model that approximates the index values and expresses the ecosystem status in continuous numbers was developed. Seventy-four quantitative and destructive samples of the upper infralittoralCystoseira crinita and coastal lagoonRuppia cirrhosa communities from tentative pristine to less impacted sites in Greece verified 10 as an ‘ideal’ EEI-c reference condition value.